Step
*
1
of Lemma
choose-formula
1. n : ℕ
2. ∀n:ℕn. ∀[m:ℕ]. (choose(n;m) * (m)! * (n - m)!) = (n)! ∈ ℤ supposing m ≤ n
3. m : {1...}
4. (m + 1) ≤ n
⊢ ((choose(n - 1;m - 1) + choose(n - 1;m)) * (m)! * (n - m)!) = (n)! ∈ ℤ
BY
{ Assert ⌜((choose(n - 1;m - 1) + choose(n - 1;m)) * (m)! * (n - m)!)
          = ((m * choose(n - 1;m - 1) * (m - 1)! * (n - 1 - m - 1)!)
            + ((n - m) * choose(n - 1;m) * (m)! * (n - 1 - m)!))
          ∈ ℤ⌝⋅ }
1
.....assertion..... 
1. n : ℕ
2. ∀n:ℕn. ∀[m:ℕ]. (choose(n;m) * (m)! * (n - m)!) = (n)! ∈ ℤ supposing m ≤ n
3. m : {1...}
4. (m + 1) ≤ n
⊢ ((choose(n - 1;m - 1) + choose(n - 1;m)) * (m)! * (n - m)!)
= ((m * choose(n - 1;m - 1) * (m - 1)! * (n - 1 - m - 1)!) + ((n - m) * choose(n - 1;m) * (m)! * (n - 1 - m)!))
∈ ℤ
2
1. n : ℕ
2. ∀n:ℕn. ∀[m:ℕ]. (choose(n;m) * (m)! * (n - m)!) = (n)! ∈ ℤ supposing m ≤ n
3. m : {1...}
4. (m + 1) ≤ n
5. ((choose(n - 1;m - 1) + choose(n - 1;m)) * (m)! * (n - m)!)
= ((m * choose(n - 1;m - 1) * (m - 1)! * (n - 1 - m - 1)!) + ((n - m) * choose(n - 1;m) * (m)! * (n - 1 - m)!))
∈ ℤ
⊢ ((choose(n - 1;m - 1) + choose(n - 1;m)) * (m)! * (n - m)!) = (n)! ∈ ℤ
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  \mforall{}n:\mBbbN{}n.  \mforall{}[m:\mBbbN{}].  (choose(n;m)  *  (m)!  *  (n  -  m)!)  =  (n)!  supposing  m  \mleq{}  n
3.  m  :  \{1...\}
4.  (m  +  1)  \mleq{}  n
\mvdash{}  ((choose(n  -  1;m  -  1)  +  choose(n  -  1;m))  *  (m)!  *  (n  -  m)!)  =  (n)!
By
Latex:
Assert  \mkleeneopen{}((choose(n  -  1;m  -  1)  +  choose(n  -  1;m))  *  (m)!  *  (n  -  m)!)
                =  ((m  *  choose(n  -  1;m  -  1)  *  (m  -  1)!  *  (n  -  1  -  m  -  1)!)
                    +  ((n  -  m)  *  choose(n  -  1;m)  *  (m)!  *  (n  -  1  -  m)!))\mkleeneclose{}\mcdot{}
Home
Index